2020
DOI: 10.1159/000507824
|View full text |Cite
|
Sign up to set email alerts
|

Endostatin Is an Independent Risk Factor of Graft Loss after Kidney Transplant

Abstract: Background: Endostatin is a 20-kDa C-terminal fragment of collagen XVIII, known for its ability to inhibit the proliferation of capillary endothelial cells. Previous studies suggested that circulating endostatin independently predicts incident chronic kidney disease. However, the impact of endostatin on graft loss level in kidney transplant recipients (KTRs) remains unknown. Methods: We conducted a prospective observational cohort study in 574 maintenance KTRs. Patients were followed for kidney graft loss and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…The study by Chauhan et al [78] also showed similar findings. Moreover, our present study showed that serum endostatin concentration at baseline is an independent prognostic factor of graft loss in kidney transplant recipients, demonstrating higher sensitivity than classical risk factors, such as GFR and albuminuria [79]. Also, dynamic plasma endostatin combined with other clinical data improves the predictive power of 30-day mortality in AKI [80].…”
Section: Endostatin In Kidney Diseasementioning
confidence: 50%
“…The study by Chauhan et al [78] also showed similar findings. Moreover, our present study showed that serum endostatin concentration at baseline is an independent prognostic factor of graft loss in kidney transplant recipients, demonstrating higher sensitivity than classical risk factors, such as GFR and albuminuria [79]. Also, dynamic plasma endostatin combined with other clinical data improves the predictive power of 30-day mortality in AKI [80].…”
Section: Endostatin In Kidney Diseasementioning
confidence: 50%